An Analysis of Financial Stability Indicators in European Banking: The Role of Common Factors - Clemens J. M. Kool (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
In this paper, we investigate the information content of three market indicators of financial instability using daily data on subordinated debt spreads (SND), credit default swap spreads (CDS) and implied option volatility (IV) over the period January 2001 – January 2004 for a sample of twenty major European banks. Using common factor analysis, we find for each indicator a significant common factor across banks, which we label the "market" factor. This market factor explains between 61 and 92 percent of total variation. Cointegration analysis shows that the market factor in each case is significantly related to macro financial variables such as the short term nominal interest rate, the yield spread and a European Price earning stock ratio. Hence, market risk is primarily affected by aggregate economic and financial developments which are widely seen to impact financial markets. The driving variables of market risk are different for the bond and equity markets with short-term interest rates and yield curve dominating the bond market (SND) and P/E ratio and short-term interest rate significantly influencing the equity market (IV). The CDS market seems to lie somewhat in between these two classical markets, with closer links, however, to the traditional bond market. Little evidence is found that idiosyncratic bankspecific risks are a major component of SND, CDS and IV developments.
Keywords: 330; Credit Default Swap Spreads; Risk Premium; Financial Integration